UNDERCAPITALIZATION - Walde Jáuregui, Vicente Rodolfo (2015)
To become limited companies, the initial concern is about to accomplish with the minimum percentages of contribution rates that correspond to the partners, but once society has been trying to achieve their goals find that its minimum capital is not enough to try to meet the demands for money in order to finance their activities, and therefore incurs undercapitalization, which has tried to resolve on the credit going under personal bond of the partners themselves or the banking system or to third party creditors in many cases are unsecured creditors. Ideal in the smooth operation of the business enterprise management is always projected a financial balance, but according to the samples we have analized this is one aspect of deficit in companies under analysis and therefore some theories arise to remedy this situation that sometimes have no legal protection in our commercial legal system such as the piercing the corporate veil, the prohibition of the abuse of the law or the rejection of